Impact of Thyroid Dysfunction on Red Cell Indices in a Tertiary Care Hospital - Erum Salim; Sumera Sheikh; Usman Ali; Adnan Mustafa Zubairi; Areeba Asim; Shanawer Khawaja (ziauddin University, 2020)
Background: The role of thyroid gland is to regulate the hematopoiesis in the bone marrow, which is carried out by inducing erythropoietin gene expression. The study aimed to compare red cell indices among different thyroid dysfunction disorders patients in our setup. Methods: This retrospective observational study was conducted in Ziauddin University Hospital, Karachi in Clifton campus from January 2018 to September 2018. To maintain confidentiality, patient's identification was deleted. Total number of recruited patients was 485, out of which 117 were labeled as hyperthyroid, 169 were hypothyroid and 199 were euthyroid. Subjects for all three groups were between 20-60 years old. TSH level of patients were determined by VITROS® ECiQ immunoassay analyzer by Enhanced chemiluminescence technique. Data analysis was done on SPSS 20 while, mean and Standard deviation were calculated for quantitative variables. Percentages and frequencies were calculated for categorical variables and an independent t-test was applied to see significant differences among the groups. Results: Comparison between hyperthyroid and hypothyroid groups revealed a statistically significant difference in the mean hemoglobin (p=0.036) and hematocrit (p=0.022). A statistically significant difference was also found in the RBC count (p=0.043) and hematocrit (p=0.032) while comparing hyperthyroid and euthyroid groups. There was no statistical difference between hypothyroid and euthyroid patients for any of the hematological parameters. Conclusion: There was a proven association between thyroid dysfunction and erythropoiesis, which caused hematological indices to fluctuate, therefore hematological parameters, should be monitored in patients with thyroid diseases. Keywords: Red Cell Indices; Erythropoiesis; Euthyroid; Hypothyroid; Hyperthyroid; Hematocrit; Mean Corpuscular Volume; Thyroid Stimulating Hormone.